Dextran-Polyacrylamide as Matrices for Creation of Anticancer Nanocomposite - G. Telegeev; N. Kutsevol; V. Chumachenko; A. Naumenko; P. Telegeeva; S. Filipchenko; Yu. Harahuts (International Journal of Polymer Science)
Drug targeting to specific organs and tissues is one of the crucial endeavors of modern pharmacotherapy. Controlled targeting at the site of action and reduced time of exposure of nontargeted tissues increase the efficacy of the treatment and reduce toxicity and side effects, improving compliance and convenience. Nanocarriers based on the branched copolymers dextran-graft-polyacrylamide were synthesized and characterized and were tested on phagocytic cells. It was shown that these nanoparticles are actively captured by phagocytic cells and that they are not cytotoxic. The polymer nanoparticles loaded with cisplatin at different concentrations from 0.1 to 10 μg/mL yielded dose-dependent decrease in viability of chronic myelogenous leukemia and histiocytic lymphoma cells. The lowest percentage of viable cells was observed for lymphoma cells (22%). Taking into account the fact that our nanoparticles will act mainly on malignant phagocytic cells and do not affect healthy cells, they can thus potentially be used for the therapeutic treatment of tumor cells having phagocytic activity. The effect of nanosilver on cell viability was lower than the one of polymer/cisplatin composite. The data from the cytotoxic studies indicate that nanosilver induces toxicity in cells. However, when the copolymers were conjugated to both nanosilver and cisplatin, such a nanosystem displayed less cytotoxic effect compared to the conjugates of dextran-polyacrylamide and cisplatin.